A region-dependent allele-biased expression of Dopa decarboxylase in mouse brain - Sheng, Kit-Yeng; Nakano, Toru; Yamaguchi, Shinpei (Frontiers in Cell and Developmental Biology, 2022)
Genomic imprinting is an epigenetic event in which genes are expressed only from either the paternal or maternal allele. Dopa decarboxylase (Ddc), is an imprinted gene that encodes an enzyme which catalyzes the conversion of L-dopa to dopamine. Although Ddc has been reported to be paternally expressed in embryonic and neonatal hearts, its expression pattern in the brain has been controversial. To visualize Ddc-expressing neurons, we established a knock-in mouse carrying a humanized Kusabira orange 1 (hKO1) reporter cassette at the Ddc locus (Ddc-hKO1). The expression of Ddc-hKO1 was detected in all known Ddc-positive cells in the brains of embryonic, neonatal, adult, and aged mice. We further developed an efficient purification method for Ddc-hKO1-positive neurons using a cell sorter. RNA sequencing analysis confirmed the enrichment of dopaminergic, serotonergic and cholinergic neurons in Ddc-hKO1-positive cell population recovered using this method. A detailed analysis of Ddc-hKO1 paternally and maternally derived heterozygous mice combined with immunostaining revealed that Ddc was preferentially expressed from the maternal allele in ventral tegmented area (VTA), substantia nigra pars compacta (SNc), and retrorubral field (RRF); while it was expressed from both alleles in dorsal raphe nucleus (DR). These results indicate that Ddc exhibit an allele-specific expression pattern in different brain regions, presumably reflecting the diverse regulatory mechanisms of imprinting.